Cover Feature: Electrochemical Carbon Dioxide Splitting (ChemElectroChem 6/2019). Issue 6 (27th February 2019) - Xie, Jiafang; Huang, Yiyin; Wu, Maoxiang; Wang, Yaobing
Abstract : The Cover Feature shows that CO2 reduction with value‐added chemical generation and O2 evolution take place at the three‐phase reaction interface on the surface of electrodes in a typical electrochemical CO2 splitting device. More information can be found in the Review by J. Xie et al. on page 1587 in Issue 6, 2019 (DOI: 10.1002/celc.201801716 ).